The Role of Career Guidance in Efforts to Enhance the Credibility of Vocational Education - Indra Sukma; Nurfauziah (Jurnal MEKOM (Media Komunikasi Pendidikan Kejuruan), 2026)
Purpose – This study aims to analyze the role of career guidance in strengthening professional credibility and career readiness in vocational education through a literature review approach. Vocational education is required not only to develop technical competencies but also to prepare students with professional behavior, decision-making skills, and adaptability to labor market demands. Methods – This study employed a narrative literature review design by analyzing peer-reviewed articles, books, and institutional reports published between 2020-2025. Data were collected through systematic searches in relevant academic databases and analyzed using thematic synthesis. Findings – The findings indicate that career guidance plays a significant role in enhancing students’ career decision-making abilities, employability skills, and professional attitudes. Four main themes emerged: (1) career guidance and career decision-making, (2) career guidance and employability/work readiness, (3) institutional and teacher readiness, and (4) alignment between vocational education and industry needs. Effective career guidance contributes to self-awareness, career planning, and smoother school-to-work transitions. Research implications – The study concludes that structured and sustainable career guidance programs are essential for strengthening professional credibility in vocational education. Implications highlight the need for integrating career guidance into curriculum design and strengthening collaboration between schools and industry Originality – The originality of this study lies in integrating career guidance and professional credibility within vocational education contexts.